PERBAIKAN MUTU BUAH JERUK KEPROK TERIGAS MELALUI TEKNOLOGI PENGELOLAAN AIR DAN PEMUPUKAN DI KABUPATEN SAMBAS, KALIMANTAN BARAT - Purba, Tommy -; Zuhran, M; Supriyanto, Arry (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2016)
One of the problems facing farmers tangerine orange terigas in thousand sambas is the low quality fruit.It is believed caused by fluctuations extreme levels water, temperature, moisture land, and absorption hara. This research aims to get quality orange fruit either through reduction fluctuations the water level, temperature, and moisture land and fertilizers enough to plants. Research is applied in Sambas District. Draft research use split plot design consisting of 2 main namely land with trenches experience and land with trenches not experience, each consisting of three sons petak: 1 ) fertilizer inorganic ( technology farmers ), 2 ) fertilizer inorganic organic fertilizers + mulching, and 3 fertilizer inorganic + organic fertilizers mulching + Â ( Ca + B ). Research repeated 4 times with unit experiment 10 trees.The result showed that watering trench of land in summer followed by administering fertilizer able to improve quality fruit tangerine orange terigas namely dehiscent fruit, diameter fruit ( grade ), levels acid ( % ) and sugar content ( brix ).